The perceptions of the Ilonggos on the issue of changing the form of government from a Unitary Republican State to a Federal Parliamentary Form of Government - Famatid, Marsha Caridad L.; Antonillas, Marissa S.; Villa, Anna Niña U. (2006)
The object of the study is to know the perception of the Ilonggos on the issue of changing the form of government from a Unitary Republican System to a Federal Parliamentary form of Government. The researchers used variables such as the age, gender, civil status, income , employment status, education and religion to know if these variables affect the perceptions of the Ilonggos on the issue. The study was conducted with 100 purposively selected respondents who were personally given the data-gathering instrument. The data then gathered were statistically analyzed and interpreted. Based on the study, it was answered by mostly women and Roman Catholics. many of the Ilonggos are aware of the present system. However, most of them do not know the implications that the Federal parliamentary System brings. Though they may be aware that the Federal Parliamentary System connotes economic progress, some other positive implications are not asserted. Education is the single most influential factor on the perceptions of the Ilonggos, the rest are slightly considered as a factor of a person's perception. It is believed that most of the Ilonggos are not aware of the new system of governance being considered, therefore, most of them are not in favor of changing the present system. It is then highly recommended that there should be greater advocacy by the proponents of the Federal Parliamentary System to create a positive change in our country in such a case.
Research Paper (Management 299-Research Methods in Management). -- [Iloilo City : UPV-CM], February 27, 2006.